Frictional properties of the active San Andreas Fault at SAFOD: Implications for fault strength and slip behavior. Issue 7 (14th July 2015) - Carpenter, B. M.; Saffer, D. M.; Marone, C.
Abstract We present results from a comprehensive laboratory study of the frictional strength and constitutive properties for all three active strands of the San Andreas Fault penetrated in the San Andreas Observatory at Depth (SAFOD). The SAFOD borehole penetrated the Southwest Deforming Zone (SDZ), the Central Deforming Zone (CDZ), both of which are actively creeping, and the Northeast Boundary Fault (NBF). Our results include measurements of the frictional properties of cuttings and core samples recovered at depths of 2.7 km. We find that materials from the two actively creeping faults exhibit low frictional strengths (μ = 0.1), velocity‐strengthening friction behavior, and near‐zero or negative rates of frictional healing. Our experimental data set shows that the center of the CDZ is the weakest section of the San Andreas Fault, with μ = 0.10. Fault weakness is highly localized and likely caused by abundant magnesium‐rich clays. In contrast, serpentine from within the SDZ, and wall rock of both the SDZ and CDZ, exhibits velocity‐weakening friction behavior and positive healing rates, consistent with nearby repeating microearthquakes. Finally, we document higher friction coefficients (μ > 0.4) and complex rate‐dependent behavior for samples recovered across the NBF. In total, our data provide an integrated view of fault behavior for the three active fault strands encountered at SAFOD and offer a consistent explanation for observations of creep and microearthquakes along weak fault zones within a strong crust.